Molecular characterization of Leishmania DNA from archived giemsa-stained slides of patients from Salta, Argentina - Almazán, María Cristina (2019)
Cutaneous leishmaniasis is endemic in the northwestern province of Salta in Argentina. Leishmania DNA from Giemsa-stained slides of up to 12 years in storage of patients from a University based reference center in Oran, Salta was characterized through PCR-Restriction Fragment Length Polymorphism (RFLP). One hundred smears from individuals with suspicious lesions and epidemiologic exposure plus microbiologic confirmation through positive microscopy were analyzed. The samples had been originally taken 2, 3, 5, 6 and 12 years prior to performing PCR-RFLP (20 samples from each year) and were maintained at room temperature in a tropical environment. All the cases were classified in a semiquantitative scale for amastigote density, and Leishmanin skin test (LST) results were included. DNA extraction was done applying lysis buffer with proteinase K, and then DNA was amplified with ribosomal internal transcribed spacer 1(ITS1) primers. PCR products were digested with HaeIII enzyme. All PCR positive smears (74/100) belonged to Viannia subgenus. A statistically significant directly proportional relationship between semiquantitative microscopy and PCR results was detected (p < 0.001). All patients had LST positive results (induration ≥ 5 mm), and the smears of those with positive but smaller induration (LST < 19 mm) had a higher proportion of positive PCR results. This study determined that smear age did not affect PCR positivity, which allows retrospective analyzes and suggests smears might be useful for molecular complementary diagnosis. Since Leishmania (Viannia) braziliensis is the main circulating species in the study area, determining Viannia subgenus in all analyzed samples confirms previous findings. PCR positivity showed statistically significant differences according to semiquantitative microscopy, highlighting the importance of parasite burden in the diagnostic sensitivity of the method. Considering that smears of patients with smaller LST induration were more positive in PCR, a negative smear from patients with positive LST response, but < 19 mm, could actually represent a false negative smear result.